The Concept Educator According To Education Of Islam - Fitri Wardani; Elsi Witria Angraini Sari (Proceeding International Seminar of Islamic Studies, 2019)
The theme of this research is Concept of Educator in Perspective of Education Islam. The reason of Problem is the Educator of Islamic Instituation still to experience the problem in applicate the concept of change for every attitude and behaviour of the participant like to inculcate the values of Islam on proses grow to formation personalities that has noble character according to Al-Quran and As-Sunnah. For every which is conducted of instituation Education Islamicis is to handle every problem that happened in concepts of Educator Islam. The purpose of this research is to created the concept of Educator Islam in order to be created that has Islamic personalities and to prevent behind of The Instution of Education Islam from the other Intituation. The method that used of this research is Library research, qualitative. It was founded that the consept of the educator are varied according to the needs of participants.